Vilanterol trifenatate, a novel inhaled long-acting beta2 adrenoceptor agonist, is well tolerated in healthy subjects and demonstrates prolonged bronchodilation in subjects with asthma and COPD - Kempsford, Rodger; Norris, Virginia; Siederer, Sarah (Pulmonary pharmacology & therapeutics, 2013)
Vilanterol (VI; GW642444M) is a novel inhaled long-acting β2-agonist with inherent 24 h activity in vitro in development as a combination with the inhaled corticosteroid fluticasone furoate for both COPD and asthma. These studies were conducted to determine the safety, tolerability, pharmacodynamics and pharmacokinetics of VI in healthy subjects and subjects with mild to moderate persistent asthma and moderate to severe COPD. Single doses of VI (25–100 μg) were given once daily to subjects with asthma and COPD and repeat doses once daily for 14 days to healthy subjects. Adverse events (AEs), vital signs, ECGs, pharmacodynamic endpoints, FEV1 and VI plasma pharmacokinetics (AUC, Cmax and Tmax) were determined following dosing. VI (25–100 μg) was well tolerated. The incidence and severity of AEs were comparable to placebo. Following VI administration there were no clinically significant abnormalities in vital signs, 12-lead ECG, Holter ECG, blood glucose or potassium. There were no statistically significant effects on QTc of single and repeat VI doses up to 50 μg; some differences were seen following the 100 μg VI dose after single and repeat dose in healthy subjects and single dose in asthmatic subjects. All VI doses produced increases in FEV1 from as early as 5 min after dosing which were maintained up to 24 h post-dose in subjects with asthma and COPD. In all subjects VI was rapidly absorbed (healthy subjects median Tmax at 5 min; asthma and COPD subjects median Tmax at 10 min) with systemic exposure increasing in an approximately dose proportional manner across the VI dose range. Marginal accumulation was seen on repeat dosing. Single doses of inhaled VI in subjects with asthma and COPD and repeat doses in healthy subjects were well tolerated with no clinically significant unwanted systemic effects. VI produced a rapid and prolonged bronchodilation over 24 h suggesting the potential for once daily administration.